Search for B+/--->[K(-/+)pi(+/-)](D)K+/- and upper limit on the b-->u amplitude in B+/--->DK+/-. - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
We search for B+/--->[K(-/+)pi(+/-)](D)K+/- decays, where [K(-/+)pi(+/-)](D) indicates that the K-/+pi(+/-) pair originates from the decay of a D0 or D (0). Results are based on 120x10(6) Upsilon(4S)-->BB decays collected with the BABAR detector at SLAC. We set an upper limit on the ratio R(Kpi) identical with[Gamma(B+-->[K(-)pi(+)](D)K+)+Gamma(B--->[K(+)pi(-)](D)K-)][Gamma(B+-->[K(+)pi(-)](D) / K+)+Gamma(B--->[K(-)pi(+)](D)K-)]<0.026 (90% C.L.). This constrains the amplitude ratio r(B) identical with|A(B--->D 0K-)/A(B--->D0K-)|<0.22 (90% C.L.), consistent with expectations. The small value of r(B) favored by our analysis suggests that the determination of the Cabibbo-Kobayashi-Maskawa phase gamma from B-->DK will be difficult.